MENINGKATKAN KEMAMPUAN GURU AGAMA KATOLIK TK. SMA MENYUSUN INSTRUMEN PENILAIAN BERBASIS HOTS MELALUI PENDAMPINGAN PENGAWAS DI MGMP KOTA MEDAN - Pitna Simanjuntak (Universitas Negeri Medan, 2021)
This study aims to improve the ability of teachers to develop HOTS-based assessment instruments through the assistance of supervisors at the Medan Catholic High School MGMP. T.P 2020/2021. This study uses the PTS method (school action research) with two cycles. The data collection tools were questionnaires and checklists with five alternative answers according to the Likert scale. The collected data were analyzed descriptively by percentage. The results of data analysis showed that the teacher's ability to develop HOTS-based assessment instruments before the action got an average score of 75 in the sufficient category, after action I increased to an average value of 87 in the good category, and after action II increased again with an average value of 92 in the very good category. . The implementation of research assistance as a Catholic religious teacher has increased, in the first cycle the average score was 73 in the sufficient category, and after the action in the second cycle, the average value was 87 in the good category. So, it can be concluded that Catholic religion teachers at the high school level in the city of Medan have the ability to develop HOTS-based assessment instruments very well. Through the assistance of researchers as supervisors of Catholic religious teachers in the city of Medan.Keywords: HOTS-based instrument, PTS